2009
DOI: 10.1080/00986440902831789
|View full text |Cite
|
Sign up to set email alerts
|

APPLICATION OF NEW ZRO2-SBA-15 MATERIALS AS CATALYTIC SUPPORTS: STUDY OF INTRINSIC ACTIVITY OF MO CATALYSTS IN DEEP HDS

Abstract: ZrO 2 -SBA-15 materials with different ZrO 2 loadings (12.5, 25, 37.5, and 50 wt.%) were prepared by incipient wetness impregnation of SBA-15 silica with zirconium (IV) n-propoxide solution and characterized by N 2 physisorption, IEP, and XRD. It was found that the dispersion of zirconia in ZrO 2 -SBA-15 samples decreased with ZrO 2 loading. Nevertheless, about 70-90% of the available support surface was covered with deposited ZrO 2 species leading to high zirconia surface, significantly higher than areas of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…The HDS of model compounds on MoS 2 in the absence of N-containing compounds has been described with pseudo-first-order kinetics. 46,47 In this work, the severe deviation of HDS from first-order kinetics is tentatively attributed to the inhibiting effect of OPA and the products of HDN. Note that in all reactions performed on MoS 2 catalysts, two regimes in conversion were differentiated: below and above 20% of OPA conversion.…”
Section: ■ Resultssupporting
confidence: 91%
“…The HDS of model compounds on MoS 2 in the absence of N-containing compounds has been described with pseudo-first-order kinetics. 46,47 In this work, the severe deviation of HDS from first-order kinetics is tentatively attributed to the inhibiting effect of OPA and the products of HDN. Note that in all reactions performed on MoS 2 catalysts, two regimes in conversion were differentiated: below and above 20% of OPA conversion.…”
Section: ■ Resultssupporting
confidence: 91%
“…It was also observed that the SBA-15 structure could accommodate the heteroatoms up to a saturation level and decreasing the / ratio from 4.54 to 1.13 did not result in any increase in the Zr content. The highest amount of loaded Zr into the SBA-15 structure in this work (16.7 wt%) is lower than that obtained by Gutiérrez et al (23.4 wt%) [29] which might be due to difference in solvent used (dry ethanol, 99.999%). A part of the alkoxide (zirconium precursor) can take part in hydrolysis as a side reaction in the presence of the water content of the absolute ethanol solvent leading to the formation of zirconium hydroxide precipitate [30].…”
Section: Elemental Analysiscontrasting
confidence: 80%
“…Powder XRD patterns for the NiMo catalyst supported on SBA-15, Zr-SBA-15 (Direct), and Zr-SBA-15 (Post) supports are shown in Figure . Diffraction due to the crystalline MoO 3 phase (JCPDS card 35-609 and JCPDS card 05-0508) ,, is observed for the NiMo catalysts supported on pure SBA-15 and Zr-SBA-15 (Direct) supports. However, XRD reflections of the crystalline MoO 3 phase disappear for the NiMo catalysts supported on Zr-SBA-15 (Post) supports prepared by the post synthesis method.…”
Section: Resultsmentioning
confidence: 98%
“…To introduce surface acidity and improve catalytic activity of mesoporous SBA-15, various heteroatoms and their oxide (such as, Al, Zr, Ti and Al 2 O 3 , ZrO 2 , TiO 2 ) have been incorporated into the SBA-15 framework. ,, Among different heteroatoms and their oxide, zirconia (ZrO 2 ) has attracted much interest. Already, zirconia has been used as a support for the hydrodesulfurization catalyst due to their following promising features: , a) zirconia supported Mo catalyst shows higher intrinsic hydrodesulfurization activity in comparison with other metal oxide (Al 2 O 3 , TiO 2 ) supported catalysts, b) zirconia possess high thermal stability, high specific mass, and extreme hardness, which are advantageous as catalyst support . However, the major disadvantage associated with pure zirconia support is low surface area and porosity, which represent a limitation in its application as hydrotreating catalyst support. ,, In order to overcome limitations associated with both SBA-15 and ZrO 2 , incorporation of ZrO 2 into the SBA-15 framework has been proven to be a better alternative. , ZrO 2 incorporation in SBA-15 (Zr-SBA-15) resulted in improving the textural property, surface acidity, stability, and dispersion of the sulfided active phases on to the support. ,, Hence, a synergistic effect can be obtained while incorporating ZrO 2 onto SBA-15, and the resulting support can be used for hydrotreating catalyst improvement.…”
Section: Introductionmentioning
confidence: 99%